Perspectives on education and pedagogy in the Swiss-German context. Contributions of Kant, Rousseau, Herbart, Pestalozzi and Natorp (Encuentros, 2022)
This article recapitulates some contributions made by a group of Swiss-German thinkers: Kant, Rousseau, Herbart, Pestalozzi, Natorp, highlighting points of confluence between these such as the anthropological nature of their notion of pedagogy and some vestiges of their pedagogical thought that are still in force, which in an illusory way are reported as ‘pedagogical innovations’. It is concluded that these discourses follow theorizations generated two centuries ago and these cannot be thought outside of the critical perspective of their historicity, at the same time that scientific autonomy of pedagogy must be recognized, although it is interdisciplinarily enriched by other social sciences, it has its objects, foundations, and epistemic status. In addition, it is remarked differences between education and pedagogy.